(untitled) (Mustansiria Dental Journal, 2018)
Back ground: All dental impressions should be disinfected before pouring to control cross contamination but disinfection may affect impression wettability. This study evaluated the effect of disinfection and the use of surfactant agent on the wettability of some silicone impression materials by contact angle registration of the gypsum slurry on flat surfaces of the impressions. Materials and methods: addition silicone regular body –automixing type- and condensation silicone (light body)with two types of disinfecting solutions 0.2% chlorhexidine gluconate and 1% povidone iodine for two disinfecting times and one surfactant agent (soap) were used in this study. Three treatment regimes were investigated: The first group of impression materials specimens was exposed to saliva for 5 minutes (control group). Second group of specimens was exposed to saliva then to disinfectant agents, and third group of specimens was exposed to saliva, disinfectants and surfactant agent (experimental groups), a computerized photographic procedure was used to measure the wettability of the specimens. Statistical analysis was performed by using t-est at p<0.05. Results: the results revealed that treatment with 0.2% chlorhexidine gluconate as a disinfectant alone or when tested with the surfactant improved the wettability of addition and condensation silicones at 30min. disinfection time ,but surfactant coating of disinfected condensation silicone produced a significant increase of the mean values at 60min. disinfection time. While treatment with 1% povidone iodine disinfectant increased the mean contact angles for both addition and condensation silicones significantly. Same result was seen when povidone iodine was used in combination with the surfactant. Conclusion: disinfection with 0.2% chlorhexidine gluconate produced a high-energy impression surfaces for both addition and condensation silicones.